Effects of Sowing Dates and Seed Rates on Sets Yield and Quality of the Red Onion (Allium cepa) cv. ‘Saggai Improved’ - Nourai, Abdalla H.; Hassan, Khadiga A.B.; Musa, Huda A.M. (University of Khartoum Journal of Agricultural Sciences, 2023)
An experiment was conducted at Shambat Research Station, Khartoum North for two growing seasons (2003/4 and 2004/5) to investigate the effects of three sowing dates (15 Dec., 15 Jan. and 15 Feb.) and five seed rates (90, 100, 110, 120 and 130 kg ha -1 ) on the yield and quality of the sets of red onion cultivar “Saggai Improved” .The first season gave the best vegetative growth, high total number and weight of sets ha -1 as well as improved set quality. High levels of seed rates increased the total number of sets ha -1 in the first season, while they had no effect on growth attributes and size grades per m-2 . However average set weight decreased when high levels of seed rates were used. Early planting date (15 Dec.) resulted in better plant growth as reflected in increased leaf number plant-1 , fresh and dry weight of sets and total fresh and dry weight. Significant increases in the total number and weight of sets ha -1 , improved set quality and set weight due to early planting were also realized